Optimalisasi Pelayanan Dan Fasilitas Kesehatan Bagi Pegawai Negeri Pada Polri: Optimalisasi Pelayanan Dan Fasilitas Kesehatan - Aziz, M Asrul; Suprapto, Heri (Pusat Penelitian dan Pengembangan Polri, 2023)
Health services are one of the basic services by the government in addition to education services and basic needs. Likewise for PNPP, especially through the Police FKTP. However, until now research on health services in Polri has been dominated by health services in hospitals. In fact, FKTP plays an important role as a gate keeper in the national health service system. As a result, little is known about the Police's FKTPs. This study aims to determine health services in the Police FKTP in terms of four aspects, namely the availability of health facilities, the types of health services and their quality, the PNPP's understanding of health insurance owned and its utilization, and the constraints in managing the Police FKTPs in the sample Polda ranks. Based on the use of mixed methods with a triangulation strategy, the data collection for this research was carried out by distributing questionnaires with a Google form, FGD, and observing the Police FKTP. The sample Polda consisted of 11 Polda, namely Polda Aceh, Riau, Yogyakarta Special Region, South Kalimantan, West Sulawesi, West Papua, Maluku, West Nusa Tenggara, East Kalimantan, Bangka Belitung Islands, and Gorontalo. The number of respondents who filled out the questionnaire was 23,643 police personnel. The FGD at Polda was conducted with the Head of BPJS Kesehatan Branch Office, Karo SDM, Head of HR, Kabiddokkes, Head of Hospital, Head of Polyclinic. The FGD at the Polres was conducted with the Kapolres Wakapolres, Head of BPJS Branch Office, Head of HR, Kasidokkes.